Penerapan Metode Six Sigma dalam Upaya Mengurangi Cacat pada Produk Cap Flip Top - Okta Tri Wulandari; Widya Setiafindari (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2023)
PT X is a company engaged in manufacturing bottle caps such as cap flip top ?50-8 white snap on products. In the production process at PT X in August 2022, there is a problem related to the level of defects in the cap flip top ?50-8 white snap products which increases and exceeds the regulatory limit (5%), reaching 10% or 65,707 units of the total production of 658,000 units. Based on the problem of the high percentage of defects, it is necessary to carry out a quality control using six sigma to determine the level of defects that occur, to look for factors affecting the highest defects and to provide suggestions for improvements. From the results of the analysis using six sigma, it is found that the highest level of defects, namely the type of black spot defects, is 45,413 pcs with a percentage of 69.11% and the average sigma value obtained is 3,022. Next, the results of the fishbone diagram   analysis show that the factors causing black spot defects are machines, materials, humans, media, and methods. From each of these causal factors, improvement can be given using 5W + 1H to reduce black spot defects that occur in the cap flip top ?50-8 white snap on in the next production process.